In situ polymerization of styrene into a PMMA matrix by using an extensional flow mixing device: A new experimental approach to elaborate polymer blends. (27th January 2017) - Pierrot, François Xavier; Ibarra-Gómez, Rigoberto; Bouquey, Michel; Muller, René; Serra, Christophe A.
Abstract: The present work consisted in the in situ polymerization of a liquid monomer (styrene) into a melt polymer matrix (PMMA) as an innovative method to prepare polymer blends at fine dispersions. That was possible by using an original mixing/reactor device called RMX ®, which significantly develops extensional flow, greatly enhancing the mixing efficiency. Resultant morphology was characterized by TEM and average particle sizes were obtained by means of image analysis. A high distributive efficiency was observed at very fine dispersed phase morphology, tens of nanometers in diameter, in fact, in the absence of compatibilizing agents. It was found, by comparing self (thermal) and peroxide-initiated systems, that morphology strongly depends on the balance between polymerization rate and monomer diffusion into the polymer matrix (as enhanced by PMMA solubility into styrene) during mixing. Finally, a comparison of morphology between compounds prepared by reactive blending and those elaborated by conventional melt mixing was done. Graphical abstract: Highlights: A new approach of reactive blending based on in-situ polymerization. Use of a mixer based on extensional flow named RMX ® . Obtaining of nanometer particle size without the aid of compatibilizers.